(untitled) (Docentes 2.0 Journal, 2025)
Childhood malnutrition affects cognitive development and limits academic performance, especially in the Amazon region of Ecuador, where limited access to nutritious food exacerbates this situation for thousands of students aspiring to improve their economic conditions. The study aimed to analyze how a history of malnutrition affects students by assessing their cognitive functions and academic adaptation skills. A research study was conducted within the positivist paradigm, using the inductive method, with a quantitative approach and a non-experimental, descriptive, and cross-sectional design. One hundred university students from the Amazon State University (UEA) with and without a history of malnutrition (n = 50 per group), selected by purposive sampling, were evaluated using memory, concentration, and attention tests, as well as analysis of biomarkers of iron, zinc, and vitamin B12. Structured questionnaires were applied to assess eating habits and academic stress levels. The results showed that students with a history of malnutrition obtained significantly lower scores in working memory (M = 32.4; SD = 4.3) compared to their peers without a history (M = 40.7; SD = 5.1; t (98) = 5.64; p < 0.001). They also presented higher levels of academic stress and deficiencies in essential biomarkers for cognitive functions. These findings are consistent with previous studies that show how malnutrition compromises brain development and affects cognitive skills essential for meaningful learning, generating long-term academic difficulties.